2015
DOI: 10.1088/0029-5515/55/5/053029
|View full text |Cite
|
Sign up to set email alerts
|

One-dimensional modelling of limit-cycle oscillation and H-mode power scaling

Abstract: To understand the connection between the dynamics of microscopic turbulence and the macroscale power scaling in the L-I-H transition in magnetically confined plasmas, a new time-dependent, one-dimensional (in radius) model has been developed. The model investigates the radial force balance equation at the edge region of the plasma and applies the quenching effect of turbulence via the E × B flow shear rate exceeding the shear suppression threshold. By slightly ramping up the heating power, the spatio-temporal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 54 publications
(81 reference statements)
2
27
0
Order By: Relevance
“…An additional complication is the treatment of the transition between the closed and open field-line region requiring correct implementation of sheath boundary conditions for the SOL. Several modeling results show a poloidal flow increase concomitantly with an ion pressure-gradient increase at the transition [64,65]. Other simulations results do not show a clearly separated trigger signature in advance of the increase in the pressure gradient/diamagnetic flow [70].…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…An additional complication is the treatment of the transition between the closed and open field-line region requiring correct implementation of sheath boundary conditions for the SOL. Several modeling results show a poloidal flow increase concomitantly with an ion pressure-gradient increase at the transition [64,65]. Other simulations results do not show a clearly separated trigger signature in advance of the increase in the pressure gradient/diamagnetic flow [70].…”
Section: Discussionmentioning
confidence: 90%
“…This condition depends on the Reynolds stress, the flow-damping rate, and the pressure-gradient scale length. A rigorous analysis of the predator-prey system described in [26] can be found in the literature [65,78] but is beyond the scope of this paper. However, a simple model for the energy exchange between turbulence and flows is discussed in section 5.…”
Section: L-h Transitions Initiated Via Lcomentioning
confidence: 99%
See 1 more Smart Citation
“…These results suggest that the transition behaviour might be different even if input power is marginal to the transition threshold. A recent numerical approach of transition dynamics ( [43], and references therein), which demonstrated that LCOs appear when the input power is close to the transition threshold, should take more variations into consideration. This may not be the effect of the wall changes, since the wall material in the divertor was unchanged and heavy lithium wall coating was conducted in both campaigns.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Ordinary differential equation (ODE) models for the L-H transition are based on the predator-prey relationship between zonal flow and turbulent flow, and incorporate a potential energy related to the pressure profile as an additional state variable [4][5][6][7][8][9][10][11][12] . Miki et al 13 and Wu et al 14 have both suggested 1D partial differential equation (PDE) models for the L-H transition based on this predator-prey relationship.…”
Section: Introductionmentioning
confidence: 99%